Cost Components of Treatment Protocols of Haemophilia Patients with Inhibitors Using Bypassing Agents in Iran: Cost Components of Treatment Protocols of Haemophilia Patients - Mina Golestani; Peyman Eshghi; Abdol Majid Cheraghali; Hamid Reza Rasekh; Jamshid Salamzadeh; Ali Imani (Iranian Journal of Pharmaceutical Sciences, 2016)
Bypassing agents are the most commonly used medicines for the treatment of hemophilia patients with inhibitors. The aim of this study is to identify the cost components of management of bleeding vents in hemophilia patients with inhibitors in Iran.This study is a cross-sectional study using a bottom-up approach to determine the cost components of treatment of hemophilia patients with inhibitors via ascertaining of all direct medical and non-medical costs.The evaluatiion of cost components of 20 patients with 40 episodes of bleeding showed that the price of medicines used is responsible for more than 96% and 97% of costs in treatment of hemophilia patients using FEIBA® and AryoSeven, respectively. The results of this study showed that cost of treating one bleeding episode in hemophilia A patients with high antibody titer using FEIBA is 376 USD compared to 857.3 USD for AryoSeven®.Despite the small number of hemophilia patients with inhibitor in Iran, due to high cost of treating these patients, it is very important to choose the cost-effective treatment protocol for the treatment of these patients.